Deep CO2 in the end-Triassic Central Atlantic Magmatic Province - Manfredo Capriolo; Andrea Marzoli; László E. Aradi; Sara Callegaro; Jacopo Dal Corso; Robert J. Newton; Benjamin J. W. Mills; Paul B. Wignall; Omar Bartoli; Don R. Baker; Nasrrddine Youbi; Laurent Remusat; et al. (Nature Communications, 2020)
Many major mass extinction events have been associated with large volcanic eruption events, with the argument that large volumes of volcanic degassing could trigger past global climate changes. Here, the authors find that during the end-Triassic extinction event volcanic pulses emitted large amounts of CO2 comparable to projected anthropogenic emissions for the 21st century in the future 2 °C warming scenario.